Pengembangan Framework untuk Mengukur Tingkat Keberhasilan Implementasi Reverse Logistics - Farida Pulansari; Dwi Sukma Donorianto; Iriani Iriani (Jurnal Teknik Industri, 2015)
Electronic Waste (E-waste) is growing attention at the end of this decade. E-waste must be managed properly. E-waste has a negative impact on the environment. E-waste contain B3 (Bahan Berbahaya dan Beracun). Reverse Logistics (RL) is one approach that able to solve these problems. The use of secondary materials through the process of remanufacturing, recycling, refurbishing, recondition are strategy to minimizing the number of e-waste. Many companies claim successfully implementing of RL. However, there are no clear indicators or parameters to assess the success of RL implementation. In this research we propose the design of reverse logistics maturity framework. Grounded Theory (GT) is chosen to design this framework. GT is a research methodology involving the construction of theory based on phenomena. This framework will be divided into five levels of maturity: Level Conventional, Managed, Developed, Innovative and Optimized. Results of research from three consumer electronics companies were in the Level Managed.